2020
DOI: 10.3390/catal10080928
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Removal by Advanced Electrocoagulation Processes: The Role of Oxidants Generated and Kinetic Modeling

Abstract: Arsenic (As) is a naturally occurring element in the environment that poses significant risks to human health. Several treatment technologies have been successfully used in the treatment of As-contaminated waters. However, limited literature has explored advanced electrocoagulation (EC) processes for As removal. The present study evaluates the As removal performance of electrocoagulation, electrochemical peroxidation (ECP), and photo-assisted electrochemical peroxidation (PECP) technologies at circumneutral pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…During the EC process, for the treatment of As, the dissolved form of As probably reacted with released ions Fe and Al in both electrode configurations and could have formed arsenate and/or arsenite that could have adsorbed and accumulated on the hydroxides of (Fe) and (Al) and residues [40]. Main anodic reactions with Fe or Al electrode: First, oxidation of Fe to ferrous ion occurs, and, depending on the anode potential, its subsequent oxidation to Fe ion may occur, as shown in the following equations [22,28,41,42]. With the Fe electrode configuration at the anode side of the EC system, the reactions (Equations ( 1)-( 6)) occurred to initi- Main anodic reactions with Fe or Al electrode: First, oxidation of Fe to ferrous ion occurs, and, depending on the anode potential, its subsequent oxidation to Fe ion may occur, as shown in the following equations [22,28,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the EC process, for the treatment of As, the dissolved form of As probably reacted with released ions Fe and Al in both electrode configurations and could have formed arsenate and/or arsenite that could have adsorbed and accumulated on the hydroxides of (Fe) and (Al) and residues [40]. Main anodic reactions with Fe or Al electrode: First, oxidation of Fe to ferrous ion occurs, and, depending on the anode potential, its subsequent oxidation to Fe ion may occur, as shown in the following equations [22,28,41,42]. With the Fe electrode configuration at the anode side of the EC system, the reactions (Equations ( 1)-( 6)) occurred to initi- Main anodic reactions with Fe or Al electrode: First, oxidation of Fe to ferrous ion occurs, and, depending on the anode potential, its subsequent oxidation to Fe ion may occur, as shown in the following equations [22,28,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Main anodic reactions with Fe or Al electrode: First, oxidation of Fe to ferrous ion occurs, and, depending on the anode potential, its subsequent oxidation to Fe ion may occur, as shown in the following equations [22,28,41,42]. With the Fe electrode configuration at the anode side of the EC system, the reactions (Equations ( 1)-( 6)) occurred to initi- Main anodic reactions with Fe or Al electrode: First, oxidation of Fe to ferrous ion occurs, and, depending on the anode potential, its subsequent oxidation to Fe ion may occur, as shown in the following equations [22,28,41,42]. With the Fe electrode configuration at the anode side of the EC system, the reactions (Equations ( 1)-( 6)) occurred to initiate the EC process and removal of As and other dissolved ionic, organic, inorganic and elemental species [22,43], as follows:…”
Section: Discussionmentioning
confidence: 99%
“…The removal of hardness through electrocoagulation has been proposed to occur through a coprecipitation reaction mechanism at the cathode. This coprecipitation reaction allows for the formation of Mg­(OH) 2 /MgCO 3 and CaCO 3 (pH > 10). , The aluminum polyhydroxide species can also facilitate hardness removal. , Previous studies of electrocoaglation have demonstrated that it can be used for organic contaminants, heavy metal removal, as well as fluoride removal. …”
Section: Introductionmentioning
confidence: 99%